2015
DOI: 10.1165/rcmb.2014-0431oc
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Airway Epithelium Cell Activation by Mesenchymal Stromal Cells Ameliorates House Dust Mite–Induced Airway Inflammation in Mice

Abstract: Allergic asthma is underpinned by T helper 2 (Th2) inflammation. Redundancy in Th2 cytokine function and production by innate and adaptive immune cells suggests that strategies aimed at immunomodulation may prove more beneficial. Hence, we sought to determine whether administration of mesenchymal stromal cells (MSCs) to house dust mite (HDM) (Dermatophagoides pteronyssinus)-sensitized mice would suppress the development of Th2 inflammation and airway hyperresponsiveness (AHR) after HDM challenge. We report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 49 publications
3
27
1
Order By: Relevance
“…MSCs have been shown to ameliorate allergic airway inflammation in mouse models of asthma (58–60). Thus, it is likely that the exacerbated inflammation in AhR −/− mice may be due to the insufficient number of MSCs present in the lungs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have been shown to ameliorate allergic airway inflammation in mouse models of asthma (58–60). Thus, it is likely that the exacerbated inflammation in AhR −/− mice may be due to the insufficient number of MSCs present in the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs have a remarkable capacity to modulate immune responses and change the progression of different inflammatory diseases through the release of a variety of bioactive molecules (7779). Recent studies have suggested that MSCs ameliorate allergic airway inflammation in mouse models of asthma (58–60). This study illustrated that MSCs were decreased in CRE-challenged AhR −/− mice with exacerbated lung inflammation, but increased in TCDD-treated CRE-challenged mice with ameliorated lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of IL-1a or HMGB1 is able to block production of the pro-Th2-cell-derived cytokines IL-33, IL-25, and GM-CSF in the lung after HDM administration, showing that the epithelial alarmins act very upstream in the allergic type 2 cascade Ullah et al, 2014;Willart et al, 2012). Adoptive transfer of mesenchymal stem cells has been shown to suppress features of asthma, via interleukin-1 receptor antagonist (IL-1RA)-mediated suppression of IL-1a and HMGB1 (Duong et al, 2015). Increased amounts of HMGB1 are found in the skin of mice with AD lesions (Karuppagounder et al, 2014(Karuppagounder et al, , 2015.…”
Section: Epithelial-derived Damps and Alarmins Promote Th2-cell-mediamentioning
confidence: 99%
“…increased TGF-b levels seem to mobilize more MSCs to the airways, demonstrating how allergen's particularities influence MSCs in vivo 37. In HDM model, epithelial activation by proteases exacerbate lung inflammation, nevertheless, MSC administered prophylactically still prevents asthma by modulating epithelial cells 38,39. The obstacles for cell therapy seem to be highlighted when established asthma models are improved using relevant allergens.…”
mentioning
confidence: 99%